Laboratorios Virtuales: una alternativa para mejorar el rendimiento de los estudiantes y la optimización de recursos económicos - Encalada Noboa, Jorge (2016)
In teaching science the laboratory activities increase students interest, so that favors learning. However, due to the lack of laboratories in educational institutions, or in turn, inadequate instrumentation in laboratories, laboratory practices are rarely performed in schools and colleges in the country. Nevertheless, due to the results of the rapid development in information and communications technology, these experiments can be performed quickly and with similar or better results than those obtained with well-equipped laboratories. In this study itis presented the use of virtual simulations related to the units of the first year of the General Unified Baccalaureate of Ecuador with students of the aforementioned year and its effects are analyzed in academic achievement thereof. To this end, was performed an intervention with six virtual experiments used in the experimental group. The result of this study showed that virtual laboratory applications had positive effects on academic performance of students, compared with traditional teaching methods.